The protective role of adipogenic lineage precursors in maintaining bone marrow redox homeostasis in a mouse model of prenatal dexamethasone exposure - Jianwen Su; Sushuang Ma; Mankai Yang; Jichang Wu; Yijie Chen; Mingchao Jin; Qin Shi; Xianrong Zhang (Redox Biology)
Bone marrow adipogenic precursors play important roles in bone metabolism in both young and adult mice, but their contributions to early long bone development remains poorly understood. In this study, we elucidate the role of bone marrow adipocyte lineage precursors in modulating bone marrow redox homeostasis through the secretion of fibulin-5 (Fbln5), using a prenatal dexamethasone exposure (PDE) mouse model. Our previous research demonstrates that PDE induces cellular senescence in the bone marrow, resulting in long bone growth retardation in young offspring. Extending these findings, we now reveal that PDE not only induces cellular senescence and impairs bone formation, but also disrupts type H vessels and reduces Adiponectin-expressing (Adipoq+) cells. Importantly, genetic ablation of Adipoq+ cells recapitulates the phenotypes observed in PDE-exposed offspring, characterized by increased cellular senescence and loss of osteoblasts and osteoprogenitors during the early postnatal period, ultimately resulting in reduced trabecular bone mass in young adult mice. RNA-seq and in vivo data identify that Adipoq+ cells are a primary source of Fbln5, and that PDE significantly reduced the number of Adipoq+ cells, thereby decreasing Fbln5 expression and elevating ROS stress in bone marrow. Moreover, targeted overexpression of Fbln5 in Adipoq+ cells via adeno-associated virus effectively mitigates cellular senescence and ROS accumulation, preserves type H vessels and osteoblasts, and normalizes osteoclasts activity, thereby rescuing the long bone growth retardation caused by PDE. Collectively, these findings uncover a previously unrecognized function of Adipoq+ cells in regulating redox homeostasis within the bone marrow microenvironment during the early stages of long bone development.